Host genotype and amoxicillin administration affect the incidence of diarrhoea and faecal microbiota of weaned piglets during a natural multiresistant ETEC infection. (3rd September 2019) - Massacci, Francesca Romana; Tofani, Silvia; Forte, Claudio; Bertocchi, Micol; Lovito, Carmela; Orsini, Serenella; Tentellini, Michele; Marchi, Lucia; Lemonnier, Gaetan; Luise, Diana; Blanc, Fany; Castinel, Adrien; et al.
Abstract: Enterotoxigenic Escherichia coli (ETEC) is the aetiological agent of postweaning diarrhoea (PWD) in piglets. The SNPs located on the Mucine 4 ( MUC4 ) and Fucosyltransferase 1 ( FUT1 ) genes have been associated with the susceptibility to ETEC F4 and ETEC F18, respectively. The interplay between the MUC4 and FUT1 genotypes to ETEC infection and the use of amoxicillin in modifying the intestinal microbiota during a natural infection by multiresistant ETEC strains have never been investigated. The aim of this study was to evaluate the effects of the MUC4 and FUT1 genotypes and the administration of amoxicillin through different routes on the presence of diarrhoea and the faecal microbiota composition in piglets naturally infected with ETEC. Seventy‐one piglets were divided into three groups: two groups differing by amoxicillin administration routes—parenteral (P) or oral (O) and a control group without antibiotics (C). Faecal scores, body weight, presence of ETEC F4 and F18 were investigated 4 days after the arrival in the facility (T0), at the end of the amoxicillin administration (T1) and after the withdrawal period (T2). The faecal bacteria composition was assessed by sequencing the 16S rRNA gene. We described that MUC4 and FUT1 genotypes were associated with the presence of ETEC F4 and ETEC F18. The faecal microbiota was influenced by the MUC4 genotypes at T0. We found the oral administration to be associated with the presence of diarrhoea at T1 and T2. Furthermore, the exposure to amoxicillin resulted in significant alterations of the faecal microbiota. Overall, MUC4 and FUT1 were confirmed as genetic markers for the susceptibility to ETEC infections in pigs. Moreover, our data highlight that group amoxicillin treatment may produce adverse outcomes on pig health in course of multiresistant ETEC infection. Therefore, alternative control measures able to maintain a healthy faecal microbiota in weaners are recommended.